Scalable electrochemical system for enhancing electrolytic chlorine decomposition reaction and its use and method

By using bismuth oxide-carbon-based material composite particle electrode, the problems of insufficient active chlorine yield in low-chlorine water and low electrocatalytic oxidation efficiency of traditional particle anode are solved, and the effect of efficient removal of ammonia nitrogen, organic matter and microorganisms in wastewater is achieved.

CN118598290BActive Publication Date: 2025-03-14QINGDAO UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410653261.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-03-14
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The existing electrochemical water treatment technology lacks the active chlorine yield in low-chlorine water bodies, and traditional particulate anodes have problems with competitive oxygen evolution reactions and low electrocatalytic oxidation efficiency when treating low-concentration chlorine-containing wastewater.

Method used

The bismuth oxide-carbon-based material composite particulate electrode is used as the anode, and the carbon coating and Bi2O3 doping are improved by pyrolyzed by phenolic resin, and the activity of hypochlorous acid production is enhanced, thereby enhancing the chlorine evolution performance.

Benefits of technology

It effectively promotes the production of active chlorine in low-concentration chloride ion water, improves the removal efficiency of ammonia nitrogen, organic matter and microorganisms in wastewater, reduces the generation of oxidation products, and achieves efficient water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118598290B_ABST
    Figure CN118598290B_ABST
Patent Text Reader

Abstract

The present invention relates to an expandable electrochemical system for strengthening electrolytic chlorine decomposition reaction, the system comprising an expandable anode and a cathode, the expandable anode is a granular electrode integrally filled in the anode area of ​​an electrolytic reactor or a granular electrode integrally filled in a water-permeable cavity; the granular electrode is constrained and filled according to the size of the electrolytic reactor or the electrode area / volume required for electrolysis; the granular electrode is a bismuth oxide-carbon-based material composite granular electrode. The system of the present application utilizes low voltage to achieve electrode strengthening to produce active chlorine, does not generate secondary pollution, reduces costs and realizes full utilization of resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater treatment equipment and materials, and in particular to an expandable electrochemical system for enhancing electrolytic chlorine decomposition reaction and a use and method thereof. Background Art

[0002] In the wastewater treatment process, the removal of ammonia nitrogen, organic matter and microorganisms is a key link to ensure that the water quality meets the standards. If organic matter is discharged directly without treatment, it will have a long-term impact on the aquatic ecology; and microorganisms may carry pathogens and pose a threat to human health. At the same time, the control of microorganisms in the circulating water system is also essential to ensure stable water quality and long-term operation of the system.

[0003] Electrochemical oxidation technology is a new and green water treatment technology. It is often used for the oxidation and removal of COD and ammonia nitrogen in industrial wastewater or for sterilization of circulating water systems. However, when the chloride ion concentration in water is low, the active chlorine production is low, and efficient treatment of the water body cannot be achieved. How to promote the production of active chlorine in low-chloride water bodies is a technical difficulty in the field of electrochemical water treatment. Compared with two-dimensional plate electrodes, three-dimensional electrodes have the advantages of large reaction area and high mass transfer and diffusion efficiency. However, common particle anodes (activated carbon, graphite, metal particles with catalytic coating, etc.) have two main problems when treating low-concentration chlorine-containing wastewater: (1) Due to the competitive oxygen evolution reaction on the anode, the Faraday efficiency of in-situ chlorine production is not high, especially when the solution contains Cl - When the concentration is less than 20 mM, the active chlorine production is insufficient; (2) the electrocatalytic oxidation efficiency is low. Therefore, it is necessary to find a method suitable for low Cl - The granular materials for efficient treatment of concentrated water bodies have guiding significance for research and engineering applications in the field of electrochemical water treatment. Summary of the invention

[0004] To solve the above problems, the present invention provides an expandable electrochemical system for enhancing the electrolytic chlorine decomposition reaction, the system comprising an expandable anode and a cathode, the expandable anode being a granular electrode integrally filled in the anode area of ​​the electrolytic reactor or a granular electrode integrally filled in a water-permeable cavity; the granular electrode is constrained and filled according to the size of the electrolytic reactor or the electrode area / volume required for electrolysis; the granular electrode is a bismuth oxide-carbon-based material composite granular electrode.

[0005] Based on the above scheme, the bismuth oxide-carbon-based material composite particle electrode is prepared by the following method:

[0006] (1) pouring carbon-based material powder, bismuth oxide powder and anhydrous ethanol into a ball mill, grinding the mixture, and drying to a constant weight to obtain a mixed powder;

[0007] (2) The phenolic resin is mixed with the mixed powder obtained in the previous step to form a mud block, which is then formed into cylindrical particles with a particle size of 5 mm to 40 mm; the prepared cylindrical particles are dried at 100° C. for 10 h, and then oxidized and annealed at 600° C. to obtain bismuth oxide-carbon-based material composite anode particles.

[0008] Based on the above solution, the cathode is a stainless steel mesh.

[0009] Based on the above scheme, the weight ratio of anhydrous ethanol to carbon-based material powder is 10:24-25; the doping amount of bismuth oxide powder is 5wt% of the total amount, and the total amount refers to the amount of carbon-based material and bismuth oxide.

[0010] Based on the above scheme, the mass ratio of carbon-based material powder to phenolic resin is 2:5.

[0011] Based on the above solution, the carbon-based material is graphite, carbon black or activated carbon.

[0012] The present application also provides a use of the above-mentioned scalable electrochemical system for enhanced electrolytic chlorine decomposition reaction. Specifically, the above-mentioned system is used to treat wastewater containing low concentrations of chloride ions, and the wastewater may also contain at least one of ammonia nitrogen, organic matter and microorganisms.

[0013] Based on the above scheme, the low concentration of chloride ions refers to a chloride ion concentration of 1-20 mM.

[0014] The present application also provides a method for enhancing the electrolytic chlorination reaction to purify wastewater containing low-concentration chloride ions. Using the above-mentioned scalable electrochemical system for enhancing the electrolytic chlorination reaction, the wastewater may also contain at least one of ammonia nitrogen, organic matter and microorganisms.

[0015] Based on the above scheme, the low concentration of chloride ions refers to a chloride ion concentration of 1-20 mM.

[0016] The present application discloses an expandable electrochemical system for enhancing electrolytic chlorine decomposition reaction, which has a simple structure and can directly load the particle electrodes into the particle electrodes in the anode area of ​​the electrolytic reactor or load the particle electrodes as a whole in a water-permeable cavity, and can perform constrained loading according to the actual size of the electrolytic reactor or the electrode area or volume required for electrolysis.

[0017] The particle electrode used in the system of this application is coated with carbon-based materials after phenolic resin pyrolysis carbon, and the physical adsorption performance is significantly improved; the doping of catalyst Bi2O3 enhances the enrichment of chloride ions on the surface of the carbon-based electrode and improves the electrocatalytic activity of the carbon-based anode in producing hypochlorous acid. The enhancement of chlorine evolution performance can be attributed to its absorption of aqueous Cl -This is due to the open pore structure of the Bi2O3 crystal surface; the design of the bismuth oxide-carbon-based composite particle anode is conducive to Cl - The transport and adsorption of chlorine promotes charge transfer and the generation of active chlorine. Therefore, the electrocatalytic system composed of the particle anode can effectively oxidize Cl in low-concentration chloride ion water. - , in situ generate strong oxidizing active chlorine species, control the oxidation direction of organic matter, reduce the generation of oxidation products, improve adsorption efficiency, and at the same time obtain the ability to efficiently remove ammonia nitrogen, organic matter and pathogenic microorganisms. The bismuth oxide-carbon-based composite particle electrode has excellent adsorption, selectivity and cycle stability. The selective adsorption performance of bismuth oxide for chloride ions is utilized to enhance the enrichment of chloride ions on the surface of the composite carbon-based electrode and improve the electrocatalytic activity of the carbon-based composite anode to produce hypochlorous acid. The prepared composite particle electrode is loaded between the cathode and cathode as a sensing electrode or directly made into an anode by a physical binding method, which not only shows excellent Cl - The invention shows the prospect of replacing traditional carbon-based materials to treat low-concentration chlorine-containing wastewater, and solves the problems of low efficiency of traditional carbon-based anode electrocatalytic oxidation and low yield of active species in low-concentration chloride ion water.

[0018] The present invention also has the advantages of low energy consumption and green environmental protection. After the impurity removal process, it can be recycled and put into the system again, and the effect is still very good. The electrode is strengthened to produce active chlorine using low voltage, which will not cause secondary pollution, reduce costs and realize full utilization of resources. The preparation method of the present invention is simple and easy to implement, and is easy to promote on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a schematic diagram of the structure of the expandable electrochemical system in Example 1 of the present application (one anode);

[0021] Figure 2 This is a schematic diagram of the structure of the expandable electrochemical system in Example 1 of the present application (two anodes)

[0022] Figure 3 This is a schematic diagram of the structure of the expandable electrochemical system in the form of being filled in a water-permeable cavity in Example 1 of the present application;

[0023] Figure 4This is a graph showing the stability test results of the electrode during five cycle tests in Example 4 of the present application;

[0024] Figure 5 This is a diagram showing the removal effects of ammonia nitrogen, phenol, and COD in Example 4 of the present application;

[0025] Figure 6 This is a graph showing the change in the generation of active chlorine over time during the reaction process in Example 4 of the present application;

[0026] Figure 7 The reaction mechanism diagram of removing ammonia nitrogen from bismuth oxide-graphite composite particle anode;

[0027] Figure 8 This is a diagram showing the removal effect of Bacillus subtilis in Example 5 of the present application. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] like Figure 1 As shown, the present application provides an expandable electrochemical system for enhancing electrolytic chlorine decomposition reaction, characterized in that it includes an expandable anode and a cathode, the expandable anode is a granular electrode filled as a whole in the anode area of ​​the electrolytic reactor or a granular electrode filled as a whole in a water-permeable cavity; the granular electrode is constrained and filled according to the size of the electrolytic reactor or the electrode area or volume required for electrolysis; the granular electrode is a bismuth oxide-carbon-based material composite granular electrode.

[0031] A water-permeable cavity refers to a cavity having a channel (such as a mesh, strip holes, or slits) on the wall thereof through which water can be exchanged or migrated.

[0032] like Figure 1 As shown, bismuth oxide-carbon-based material composite particles are loaded in the anode region of the electrolytic reactor, and the whole constitutes the anode of the reactor. The bismuth oxide-carbon-based material composite particles are constrained and loaded according to the size of the electrolytic reactor or the electrode area or volume required for electrolysis. Figure 1 The water inlet of the electrolytic reactor does not need to be specifically limited, and water can be introduced from the upper part, lower part or side of the anode chamber, or from the upper part, lower part or side of the cathode chamber ( Figure 1 The water discharge method can be overflow.

[0033] based on Figure 1In the electrolytic reactor style, multiple anode regions and cathode regions can be set in the electrolytic reactor (such as Figure 2 As shown), an appropriate amount of bismuth oxide-carbon-based material composite particles can be filled in each anode region as required. Figure 1 same, Figure 2 The arrow in the figure also indicates the direction of water inlet.

[0034] The above-mentioned particle electrode filled in the water-permeable cavity can be a bismuth oxide-carbon-based material composite particle confined in a water-permeable cavity, specifically as follows Figure 3 shown. Figure 3 In the embodiment, the bismuth oxide-carbon-based composite particles are confined in a truncated cone-shaped water-permeable cavity. In addition to this shape, the shape of the water-permeable cavity can also be spherical, cylindrical, cubic, cuboid, conical, etc., which are not shown one by one in this application. The material used to confine the bismuth oxide-carbon-based composite particles can be a metal or a non-metallic material.

[0035] As a specific embodiment, the cathode is a stainless steel mesh.

[0036] The scalable electrochemical system for enhancing the electrolytic chlorination reaction in this embodiment can be used to treat wastewater containing low concentrations of chloride ions, and the wastewater may also contain at least one of ammonia nitrogen, organic matter and microorganisms.

[0037] The low concentration of chloride ions refers to a chloride ion concentration of 1-20 mM. — When the concentration is too low, the effect will be affected; Cl — When the concentration is too high, the materials described in this study are of little use. — When the concentration exceeds 100 mM, the removal of ammonia nitrogen decreases due to the limitation of charge transfer. — At 500 mM, the reaction was slightly inhibited, which may be due to the Cl · With excess Cl — Reacts to generate anti-NH4 + -N Oxidation Species Cl2 ·- .

[0038] Example 2

[0039] The particle electrode has a great influence on the electrochemical system of the present application. Different materials have a great influence on the effect of wastewater purification. In order to achieve a better treatment effect, the present application provides a bismuth oxide-carbon-based material composite particle electrode. The carbon-based material uses graphite. Specifically, the preparation method of the bismuth oxide-graphite composite particles is as follows:

[0040] (1) pouring graphite powder, bismuth oxide powder and anhydrous ethanol into a ball mill (wherein: 5 parts of anhydrous ethanol, 12 parts of graphite powder, the doping amount of bismuth oxide powder is 5wt% of the total amount, the total amount refers to the amount of graphite + bismuth oxide, excluding anhydrous ethanol), ball milling and mixing, and then drying to constant weight (drying temperature is 100°C) to obtain a mixed powder;

[0041] (2) The phenolic resin is mixed with the mixed powder obtained in the previous step to form a mud block (the amount of phenolic resin is 30 parts relative to 12 parts of graphite powder), and then formed into cylindrical particles with a particle size of 20 mm; the prepared cylindrical particles are dried at 100° C. for 10 h, and then oxidized and annealed at 600° C. to obtain bismuth oxide-graphite composite anode particles.

[0042] The present application uses grinding, mixing, drying and calcining methods to prepare a particle electrode. The particle electrode has a large specific surface area, good conductivity and catalytic properties. It is a new type of bismuth oxide-graphite composite particle electrode, which greatly increases the reaction area of ​​the electrode and improves the reaction speed of the electrode.

[0043] Specifically, the specific surface area and pore size distribution of bismuth oxide-graphite particles were analyzed by N2 adsorption / desorption measurement and BET specific surface area method. The specific surface area (SSA) of the prepared composite particles is 38 m 2 g -1 , the average pore size is 3.20 nm, and the pore volume is 0.084 cm 3 g -1 , which is beneficial to the exposure of active sites and the rapid transport of ions.

[0044] The bismuth oxide powder used in step (1) can be directly a commercially available product or can be prepared by itself. The present application provides a method for preparing the bismuth oxide powder by itself:

[0045] Take 5.0 g of the mixture of surfactant Triton X-100 and n-hexanol (mass ratio 3:2) in a 50 mL conical flask, add 5.0 g of cyclohexane, 0.1 mol L -1 0.59 mL of Bi(NO)3 solution (the concentration of nitric acid in the Bi(NO)3 solution is 2.5 mol / L -1 , inhibit Bi 3+ The microemulsion A was obtained after mixing and shaking. The other microemulsion had the same composition as A, and the aqueous phase was treated with the same volume of 3 mol L -1 The NH3-H2O was replaced to obtain microemulsion B, which was magnetically stirred in a 20℃ constant temperature water bath for 5 min. The mixture of A and B was clear and transparent. Under magnetic stirring, microemulsion B was gradually added dropwise to A at a rate of 0.5 mL min -1As the reaction proceeds, the mixed solution gradually turns milky white. After the addition is completed, continue stirring for 1 hour and then let stand for 24 hours. The product is centrifuged and washed three times with anhydrous ethanol and secondary water to remove by-products and organic matter attached to the surface. The bismuth oxide precursor is obtained by vacuum drying at 80°C for 12 hours. The bismuth oxide precursor obtained by the reaction is calcined at 500°C to obtain bismuth oxide powder.

[0046] The bismuth oxide-graphite composite particle electrode prepared by the particle electrode preparation method of the present invention adopts graphite, carbon black, activated carbon and the like which are non-toxic, pollution-free, cheap and easily available and have a porous structure as carriers, and phenolic resin as a binder and complexing agent to dope bismuth oxide onto the graphite electrode. After being coated with phenolic resin pyrolysis carbon, the natural graphite material forms a special pore structure, and the electrochemical performance is significantly improved.

[0047] The particles use the selective adsorption performance of bismuth oxide on chloride ions to enhance the enrichment of chloride ions on the composite electrode surface and improve the electrocatalytic activity of the composite anode in producing hypochlorous acid. The problem of low electrocatalytic oxidation efficiency of traditional carbon-based anodes and low production of active species in low-concentration chloride ion water is solved, and the oxidation degradation of ammonia nitrogen and organic pollutants in low-concentration chloride ion water and the simultaneous removal of pathogenic microorganisms are efficiently achieved.

[0048] The composite particle preparation method uses grinding, mixing, drying and calcining to prepare the particle electrode. The particle electrode has a large specific surface area, good conductivity and catalytic properties, and is a new type of bismuth oxide-carbon-based composite particle electrode, which greatly increases the reaction area of ​​the electrode and improves the reaction speed of the electrode.

[0049] The bismuth oxide-carbon-based composite particle electrode complexes the active components with catalytic function on the phenolic resin and composites them with the carbon base into a particle electrode, which greatly increases the specific surface area of ​​the catalyst and also avoids the loss of the Bi2O3 active components, prolongs the service life of the particle electrode, and can be reused.

[0050] The introduction of catalyst Bi2O3 enhances the catalytic activity of the anode, allowing the electrocatalytic reaction to proceed at a lower overpotential.

[0051] The selective adsorption performance of bismuth oxide on chloride ions is utilized to enhance the enrichment of chloride ions on the composite electrode surface and improve the electrocatalytic activity of the carbon-based composite anode in producing hypochlorous acid. The present invention provides a new idea and method for improving the efficiency of electrocatalytic oxidation and increasing the yield of active chlorine in low-concentration chloride ion water, which has important practical significance and application value.

[0052] Example 3

[0053] The carbon-based material still uses graphite. The present application provides another method for preparing a bismuth oxide-graphite composite particle electrode, which is as follows:

[0054] (1) pouring graphite powder, bismuth oxide powder and anhydrous ethanol into a ball mill (wherein: 4 parts of anhydrous ethanol, 10 parts of graphite powder, the doping amount of bismuth oxide powder is 4wt% of the total amount, the total amount refers to the amount of graphite + bismuth oxide, excluding anhydrous ethanol), ball milling and mixing, and then drying to constant weight (drying temperature is 100°C) to obtain a mixed powder;

[0055] (2) The phenolic resin is mixed with the mixed powder obtained in the previous step to form a mud block (the amount of phenolic resin is 25 parts relative to 10 parts of graphite powder), and then formed into cylindrical particles with a particle size of 20 mm; the prepared cylindrical particles are dried at 100° C. for 11 hours, and then oxidized and annealed at 600° C. to obtain bismuth oxide-graphite composite anode particles.

[0056] Example 4

[0057] Use the system in Example 1 to simultaneously remove NH4 + and organic pollutant wastewater, the particle electrode used in the system is a composite particle prepared by the method of Example 2, and the structure of the system is as follows Figure 1 shown.

[0058] The experimental conditions are as follows: 200 mL of electrolyte (including 20 mM chloride ions), the size of the particle electrode is 6 cm×3 cm×2 cm; and a 6 cm×4 cm stainless steel mesh is used as the cathode.

[0059] The initial concentration was 270.5 ± 11.5 mg L -1 COD, 92 mg L -1 Phenol, 326.2±8.1mg L -1 NH4 - N simulated wastewater, ambient temperature was 25 ± 0.5 °C, electrolyte pH was not adjusted, and the effective volume of the reactor was 48 cm 3 , provided by a DC regulated power supply with 10mA cm -2 The reaction was started with a current of 200 min. The continuous flow reaction mode was used with a flow rate of 1.248 mL min -1 The electrolysis experiments were repeated three times and the rate constants were reported with 95% confidence intervals to ensure quality assurance and quality control.

[0060] This system can utilize the selective adsorption properties of bismuth oxide in the composite particle anode for chloride ions, enhance the enrichment of chloride ions on the surface of the graphite electrode, and improve the electrocatalytic activity of the graphite anode to produce hypochlorous acid, thereby achieving the removal of ammonia nitrogen and organic matter.

[0061] Specifically, the system uses ammonia nitrogen, phenol, and COD as pollutant indicators to test the removal effect of the system. The experimental results are as follows: Figure 5As shown, the results show that after 200 min of reaction and 10 mA cm -2 At a current density of - The nitrogen concentration increased from 326.2±8.1 mg L -1 Reduced to 28.5±5.4mg L -1 , phenol concentration from 92 mg L -1 Reduced to 20.5±3.4mg L -1 The continuous flow operation of the system also increased the COD from 270.5±11.5 mg L -1 Reduced to 13.5 ± 9.6 mg L -1 Experiments have shown that the system of the present invention can effectively remove ammonia nitrogen and organic matter from wastewater simultaneously.

[0062] Specifically, the free chlorine generation in the system changes with time during the reaction process as shown in the figure Figure 6 As shown, compared with the traditional system (the maximum free chlorine production of the traditional system is 24.6 mg L -1 ), the system of the present application increases the maximum output of free chlorine to 60 mg L -1 .

[0063] Specifically, the Faraday efficiency (FE) increased from 31.0% to 75.5%, and the specific energy consumption (SEC) increased from 6.07 kWhkg -1 Cl2 reduced to 2.88 kWh kg -1 Cl2.

[0064] In order to test the stability and reusability of the electrode, the current density was 10 mA / cm 2 and 40mA / cm 2 The cyclic experiment was carried out under the conditions of 5 batches of "continuous adsorption and degradation" cycle experiments and 5 batches of continuous "adsorption and degradation-desorption" cycle experiments on the bismuth oxide-carbon-based composite particle electrode. Figure 4 As shown in Figure 2, after five cycles of testing, the active chlorine concentration remained at 50-60 mg L -1 This indicates that the active components with catalytic function are complexed with phenolic resin and composited with graphite to form a particle electrode, which greatly increases the specific surface area of ​​the catalyst, while also avoiding the loss of Bi2O3 active components, extending the service life of the particle electrode and making it reusable.

[0065] Specifically, at a current density of 10 mA / cm 2 Under the condition of constant current, 5 batches of electrocatalytic oxidation degradation experiments were carried out on the bismuth oxide-carbon-based composite particle electrode, the corresponding overpotential was only 0.5V, each group of reaction was 200min, and the removal effect of ammonia nitrogen was measured. After 5 cycles of use, the electrode had a NH4- The removal rate of N was still 91%, and the particle electrode did not drop or break. The composite particle electrode showed good stability.

[0066] Specifically, at a current density of 40 mA / cm 2 Under the constant current condition, 5 batches of adsorption degradation-desorption experiments were carried out on the bismuth oxide-carbon-based composite particle electrode. Each group of reactions lasted for 200 minutes. After the reaction, the electrode was subjected to a 30-minute desorption experiment. After drying, the reaction was repeated. The results show that the removal rate of ammonia nitrogen by the bismuth oxide-carbon-based composite particle electrode remains at 90% after 5 "oxidation-desorption" cycles, and the particle electrode does not slag or break during the cycle. This shows that the composite particle electrode has good reusability.

[0067] The system of this embodiment involves the relevant mechanism of removing ammonia nitrogen by bismuth oxide-graphite composite anode particles as follows Figure 7 As shown, the ionic equation involved in the adsorption on the surface of the composite anode particles is:

[0068] Cl · +Cl - →Cl2 ·-

[0069] Cl2 ·- +Cl2 ·- →Cl2+2Cl -

[0070] Cl2 ·- +HO · →HClO+Cl -

[0071]

[0072] Specifically, the mechanism of active chlorine-mediated catalytic ammonia oxidation is as follows:

[0073] NH4 + +Cl · → · NH2+Cl - +H +

[0074] · NH2+HClO→NH2Cl+ · OH

[0075] NH2Cl+Cl · → · NHCl+Cl - +H +

[0076] · NHCl+HClO→NHCl2+ · OH

[0077] NHCl2+H2O→NOH+2H + +2Cl -

[0078] NH2Cl+NOH→N2+H + +Cl - +H2O

[0079] NHCl2+NOH→N2+2H + +2Cl -

[0080] NHCl2+NH2Cl→N2+3H + +3Cl -

[0081] Example 5

[0082] The system in Example 1 is applied to treat pathogenic microorganisms in a circulating water system; the particle electrodes used in the system are composite particles prepared by the method of Example 3, and the structure of the system is as follows: Figure 1 shown.

[0083] The experimental conditions are as follows: a DC regulated power supply provides 10 mA cm -2 The size of the particle electrode (anode) was 6 cm × 3 cm × 2 cm, and the cathode was a 6 cm × 4 cm stainless steel mesh. NaCl solution was used as the electrolyte solution (where the chloride ion concentration was 20 mM). 200 mL of the solution was used. -6 mg / g Bacillus subtilis suspension was used as simulated wastewater, and the effective volume of the reactor was 48 cm 3 , start the treatment reaction, the reaction time is 200min. The continuous flow reaction mode is adopted, and the flow rate is 1.248mL min -1 , the ambient temperature is 25±0.5℃, and the pH of the electrolyte is not adjusted.

[0084] Specifically, the microbial mass was calculated by weighing method. The filter paper was dried at 105℃ for 2 hours, which is represented by M1(g). The particle electrode of M0(g) was placed in pure water and heated at 160r min. -1 The mixture was shaken at 105 °C for 110 minutes and then filtered with dry filter paper. The filtered filter paper was dried at 105 °C for 2 hours and was expressed as M2. The mass of the crucible after drying at 105 °C for 2 hours was expressed as M3. The dried filter paper was placed in the crucible and calcined in a muffle furnace at 600 °C and recorded as M4. Microbial biomass M (mg g -1 ), and calculate the particle electrode per unit weight, repeat three times and take the average value.

[0085] Specifically, the experimental results are as follows Figure 8 As shown, the system was operated in continuous flow mode, and the Bacillus subtilis was grown from 6×10 - 6 mg / g dropped to 1.7×10 -6 mg / g.

[0086] Specifically, at a current density of 10 mA / cm 2 Under the constant current condition, 5 batches of electrocatalytic oxidation degradation experiments were carried out on the bismuth oxide-carbon-based composite particle electrode, the corresponding overpotential was 0.5V, and each group reacted for 200 minutes. The removal effect of microorganisms was measured. After 5 cycles of use, the removal rate of microorganisms by the electrode remained at 67%-70%, and the particle electrode did not fall off or break. This shows that the composite particle electrode has good stability.

[0087] Specifically, at a current density of 40 mA / cm 2 Under the constant current condition, 5 batches of degradation-desorption experiments were carried out on the bismuth oxide-carbon-based composite particle electrode. Each group of reactions lasted for 200 minutes. After the reaction, the electrode was subjected to a 30-minute desorption experiment. After drying, the reaction was repeated. The results showed that the removal rate of microorganisms by the bismuth oxide-carbon-based composite particle electrode remained at 70% after 5 "oxidation-desorption" cycles, and the particle electrode did not slag or break during the cycle. This shows that the composite particle electrode has good reusability.

[0088] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of protection of the present invention.

Claims

1. A method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine reaction, characterized in that: Using a scalable electrochemical system for enhanced electrolytic chlorine reaction, the wastewater also contains at least one of ammonia nitrogen, organic matter and microorganisms; The expandable electrochemical system for enhancing electrolytic chlorine decomposition reaction comprises an expandable anode and a non-expandable cathode, wherein the expandable anode is a particle electrode integrally filled in the anode area of ​​the electrolytic reactor or a particle electrode integrally filled in a water-permeable cavity; the particle electrode is constrained and filled according to the size of the electrolytic reactor or the electrode area / volume required for electrolysis; the particle electrode is a bismuth oxide-carbon-based material composite particle electrode; The bismuth oxide-carbon-based material composite particle electrode is prepared by the following method: (1) Pour the carbon-based material powder, bismuth oxide powder and anhydrous ethanol into a ball mill, mix them and dry them to a constant weight to obtain a mixed powder; (2) Mix the phenolic resin with the mixed powder obtained in the previous step to form a mud block, and then form cylindrical particles with a particle size of 5 mm-40 mm; the prepared cylindrical particles are heated at 100 ° C for 10 h and then at 600 ° C conditions, and oxidative annealing can obtain bismuth oxide-carbon-based material composite anode particles.

2. The method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine separation reaction according to claim 1, characterized in that: The low concentration of chloride ions refers to a chloride ion concentration of 1-20 mM.

3. The method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine separation reaction according to claim 1, characterized in that: The cathode is a stainless steel mesh.

4. The method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine separation reaction according to claim 1, characterized in that: The weight ratio of anhydrous ethanol to carbon-based material powder is 10:24-25; the doping amount of bismuth oxide powder is 5 wt% of the total amount, and the total amount refers to the amount of carbon-based material and bismuth oxide and.

5. The method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine separation reaction according to claim 1, characterized in that: The mass ratio of carbon-based material powder to phenolic resin is 2:

5.

6. The method for purifying wastewater containing low concentration chloride ions by strengthening electrolytic chlorine separation reaction according to claim 1, characterized in that: The carbon-based material is graphite, carbon black or activated carbon.

Citation Information

Patent Citations

  • Device and method for treating micro-polluted brackish water by coupling electro-adsorption to extended activated carbon

    CN108793346A

  • Three-dimensional electro-catalytic reaction equipment system based on multifunctional catalytic particle electrode

    CN114835201A